Magnetic field tuning of valley population in the Weyl phase of Nd_{2}Ir_{2}O_{7} - Itzik Kapon; Carl Willem Rischau; Bastien Michon; Kai Wang; Bing Xu; Qiu Yang; Satoru Nakatsuji; Dirk van der Marel (Physical Review Research, 2022)
The frustrated magnet Nd_{2}Ir_{2}O_{7}, where strong correlations together with spin-orbit coupling play a crucial role, is predicted to be a Weyl semimetal and to host topological pairs of bulk Dirac-like valleys. Here we use an external magnetic field to manipulate the localized rare-earth 4f moments coupled to the 5d electronic bands. Low-energy optical spectroscopy reveals that a field of only a few teslas suffices to create charge-compensating pockets of holes and electrons in different regions of momentum space, thus introducing a valley population shift that can be tuned with the field.